Comparative study of the zooplankton composition of two lacustrine ecosystems in Southwestern Amazonia - Keppeler, Erlei Cassiano [UNESP] (Universidade Estadual de Maringa, 2003)
The zooplankton communities of two lacustrine ecosystems in southwestern Amazonia (Lago Amapá and Lago Pirapora) were studied based on samples collected over an 11-month period. The general aim of the present work was to contribute to the knowledge of the zooplankton fauna in southwestern Amazonia, by studying the occurrence of certain species; and to improve the knowledge of the Rio Acre tributaries. The total number of taxa included 38 species of rotifers, 6 cladocerans and 7 copepods. Most of the species were from the rotifer family Brachionidae. Jaccard's similarity index was similar for the two lakes at 0.6964 The constancy index defined the species Keratella cochlearis, Filinia cf. terminate, Filinia opoliensis, Hexarthra intermedia braziliensis, Ceriodaphnia cornuta, Moina minuta, Diaphanosoma spinulosnm, and immature forms (nauplii and copepodites) as the constant in these lakes. The presence of zooplankton with higher number of species occupying the middle depths, during morning and night periods.
Keywords: Amazonia; Composition; Zooplankton; rain; Brazil; lake ecosystem; limnology; nonhuman; river ecosystem; seasonal variation; species differentiation; taxonomic identification; zooplankton; Brachionidae; Ceriodaphnia cornuta; Copepoda; Diaphanosoma; Filinia; Filinia opoliensis; Hexarthra intermedia; Keratella cochlearis; Moina minuta; Rotifera